Parenteral Nutrition-Associated Hyperglycemia in Noncritically Ill Inpatients Is Associated with Higher Mortality - Sofia Sarkisian; Tanis R Fenton; Abdel Aziz Shaheen; Maitreyi Raman (Canadian Journal of Gastroenterology)
BACKGROUND: Hyperglycemia is a marker of poor clinical outcomes in studies evaluating hospitalized critically ill patients.